Solar photovoltaic refrigeration assisted hydrate method carbon capture system - ZHAO RUIKAI; LI MINXIA; ZHAO LI; LI YINGLING; LI ZHENWEI; HE JUNNAN; LIU YINAN; DENG SHUAI (2016)
The invention discloses a solar photovoltaic refrigeration assisted hydrate method carbon capture system. A solar power generation device is connected with a thermoelectricity refrigeration device and an inverter, and the other end of the inverter is connected with an absorption-type refrigerating machine and various levels of compressors; after exchanging heat with the thermoelectricity refrigeration device and the adsorption-type refrigerating machine, a refrigerating medium exchanges heat with various levels of coolers and various levels of reaction kettles; and mixed gas such as industrial smoke CO2, N2 and the like successively passes through the absorption-type refrigerating machine, a primary hydrate method carbon capture system and a secondary hydrate method carbon capture system. By utilizing the solar photovoltaic refrigeration assisted hydrate method carbon capture system, the gradient utilization of energy is realized, the solar power generation is used for providing power to the thermoelectricity